View-Dependent Character Animation - Chaudhuri, Parag; Kalra, Prem; Banerjee, Subhashis (Springer London : Imprint: Springer, 2007)
Computer generated 3D animation has matured over the years into a rich and complex art form. The need to animate diverse characters has caused character animation to become an extensively researched area. Coordinating and presenting the character's movement in three dimensions to convey a specific idea to the audience, however, still remains a challenge. The animator has to employ a lot of artistic and technical skills, and often a labourious iterative trial-and-error process to get it right. It is even more difficult for the animator to generate the character's action if the point of view (i.e., the rendering camera) is also varying. Creating moving camera character animations in 3D is, however, a multi-faceted computer graphics and computer vision problem. It warrants a formal representation of the moving camera, and efficient algorithms to help author the multitude of character poses required for the animation. It is also necessary to deal with issues pertaining to camera and character pose interpolation and visualization of the association between the two. The solution to this problem has to be efficient and elegant from the perspective of a computer scientist, yet at the same time make sense and be intuitive to use. This well-researched book develops and demonstrates a framework for view-dependent animation designed to solve these issues, well illustrated with a large number of example animations to explain and illustrate this versatile technique.